Genome Sequence of the Yeast Saprochaete ingens CBS 517.90 - Hodorová, Viktória (Microbiol Resour Announc, 2019)
Chromosome-scale genome assembly of the yeast Saprochaete ingens CBS 517.90 was determined by a combination of technologies producing short (HiSeq X; Illumina) and long (MinION; Oxford Nanopore Technologies) reads. The 21.2-Mbp genome sequence has a GC content of 36.9% and codes for 6,475 predicted proteins.